2013
DOI: 10.1016/j.dnarep.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA repair in brain related disease pathology

Abstract: Oxidative DNA damage is implicated in brain aging, neurodegeneration and neurological diseases. Damage can be created by normal cellular metabolism, which accumulates with age, or by acute cellular stress conditions which create bursts of oxidative damage. Brain cells have a particularly high basal level of metabolic activity and use distinct oxidative damage repair mechanisms to remove oxidative damage from DNA and dNTP pools. Accumulation of this damage in the background of a functional DNA repair response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 84 publications
3
89
0
1
Order By: Relevance
“…Moreover, it has been shown that HSV-1 lytic infection induces Egr1 in rabbit corneal cells (40). Oxidative stress is capable of initiating the DDR (41) and is reported to enhance the expression of Egr1 (42), and HSV-1 has the ability to induce neuronal oxidative stress (43). With these observations and our data, we propose that oxidative stress and/or activation of DDR during acute HSV-1 infection of neurons stimulates p35 levels via Egr1 (Fig.…”
supporting
confidence: 66%
“…Moreover, it has been shown that HSV-1 lytic infection induces Egr1 in rabbit corneal cells (40). Oxidative stress is capable of initiating the DDR (41) and is reported to enhance the expression of Egr1 (42), and HSV-1 has the ability to induce neuronal oxidative stress (43). With these observations and our data, we propose that oxidative stress and/or activation of DDR during acute HSV-1 infection of neurons stimulates p35 levels via Egr1 (Fig.…”
supporting
confidence: 66%
“…The total number of mutations acquired during ageing is extremely high, and robust genomic technologies demonstrated that 3,000-13,000 genes per genome can be affected by 5,000-50,000 mutations (26). It is likely that such genomic alterations could be responsible for many health problems associated with ageing, such as neurodegeneration including Parkinson's and Alzheimer's disease (27,28). The comparison of reduced DNA-repair activity, accumulation of mutations, cancer incidence and fertility seems to be interesting from a biological point of view ( Figure 1).…”
Section: Biological Background Of Ageing and Impact On Cancer Formationmentioning
confidence: 99%
“…The past 50 years has seen mounting recognition of the enormous significance of DNA damage response (DDR) pathways in protecting against the harmful effects of this damage, and particularly our understanding of the DNA repair processes [1]. Indeed, we now understand the importance these pathways play in cancer avoidance, in protection against ageing and in ensuring normal development [3,4]. We now have a good understanding of the basic DNA repair processes, at least when considering their action on naked DNA.…”
mentioning
confidence: 99%